PENGARUH HALAL AWARENESS, HARGA DAN MEDIA SOSIAL INFLUENCER TERHADAP INTENSITAS BERBELANJA PADA SHOPEEFOOD DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERASI - Nuraisah; Rizal Agus; Muhammad Zuhirsyan; Nurlinda Nurlinda (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of halal awareness, price, and social media influencers on shopping intensity through ShopeeFood, with religiosity as a moderating variable. This research employs a quantitative approach using primary data obtained from questionnaires distributed to 154 Muslim students of the Accounting Department at Politeknik Negeri Medan. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that price and social media influencers have a positive and significant effect on shopping intensity, while halal awareness has no significant effect. Religiosity was found to moderate the influence of price on shopping intensity but did not moderate the influence of halal awareness. These findings suggest that price and social media influencers play an essential role in encouraging consumers’ shopping behavior through digital platforms such as ShopeeFood, while halal awareness has not yet become a dominant factor. Overall, this research contributes to the development of marketing strategies based on religious values and Muslim consumer behavior in the digital era.